Tackling Irritable Bowel Syndrome with Modern Resources – A Narrative Review - Mihai-Radu PAHOMEANU; Florin-Cristian CERCELARU; Irina Stefania DIACONU; Miruna Alexandra UNTEA; Ioana VAIPAN; Calisa ANDREEANA; Elena GHIZILA; Lucian NEGREANU (Modern Medicine)
Irritable Bowel Syndrome (IBS) is one of the most common disorders of the gut-brain axis, affecting a significant percentage of the global population. This review article explores the pathophysiological mechanisms of IBS in the context of the biopsychosocial model and neurogastroenterology, emphasizing the impact of motility disorders, visceral hypersensitivity, and altered intestinal microbiota. Recent epidemiological data is presented, highlighting the underdiagnosis of IBS and its increased incidence in young women. IBS management involves a multidisciplinary approach, including dietary modifications, psychosocial therapies, and various pharmacological options. Among these, the combination of alverine citrate with simethicone emerges as a first-line treatment due to its effectiveness in reducing symptoms. New research directions aim at more precise treatment personalization based on intestinal microbiome and specific biomarkers.